Croatian regulatory framework and actors in national regional policy - Zlatan Fröhlich (European Regional Science Association (ERSA), 2011)
Croatian regional policy is closely tied into the EU accession strategy. A major objective will be to prepare for the introduction of EU cohesion policy and the Structural Funds. The pre-accession funds will contribute to that effort. This will require a significant effort on the part of the government to strengthen the institutional base for the management of the Funds - from the centre of government to regions across the country. The National Strategy for Regional Development will be a major part of that effort. While many regional actors in Croatia perceive preparations for participation in Cohesion policy only from the standpoint of the new funding possibilities, the actual value of the policy transformation is somehow not yet fully perceived. One of the key reasons for this is that most of the policy transformation involves exclusively central-level institutions. Also, the full introduction of the new policy instruments such as programming, monitoring and evaluation, the payment system and other into the daily policy practice requires many substantial changes in the organisation of the involved institutions and this is a slow ongoing process. Regional actors are feeling the new policy trends mostly through the participation in the Instrument for Pre-accession (IPA) and other available EU programmes, but also through the changes in the national regional policy which has become much more open and inclusive for actors on sub-national levels than before. The strategy sets the context for balanced regional development both at national and sub-national level as well as draws attention to development needs of the `assisted areas' as well as counties highlighting their different development profiles. It brings together the main analytical parts: policy framework, institutional context and finally an assessment of the existing development interventions on county, NUTS 2 and assisted areas level.
Keywords: 330